Reconstruction of Late Glacial summer temperatures from chironomid assemblages in Lac Lautrey (Jura, France). - Heiri, Oliver; Millet, Laurent (Journal of Quaternary Science, 2005)
International audience A chironomid-July air temperature inference model based on chironomid assemblages in the surface sediments of 81 Swiss lakes was used to reconstruct Late Glacial July air temperatures at Lac Lautrey (Jura, Eastern France). The transfer-function was based on weighted averaging-partial least squares (WA-PLS) regression and featured a leave-one-out cross-validated coefficient of determination (r2) of 0.80, a root mean square error of prediction (RMSEP) of 1.53 ° C, and was applied to a chironomid record consisting of 154 samples covering the Late Glacial period back to the Oldest Dryas. The model reconstructed July air temperatures of 11-12 ° C during the Oldest Dryas, increasing temperatures between 14 and 16.5 ° C during the Bølling, temperatures around 16.5-17.0 ° C for most of the Allerød, temperatures of 14-15 ° C during the Younger Dryas and temperatures of ca. 16.5 ° C during the Preboreal. The Lac Lautrey record features a two-step July air temperature increase after the Oldest Dryas, with an abrupt temperature increase of ca. 3-3.5 ° C at the Oldest Dryas/Bølling transition followed by a more gradual warming between ca. 14 200 and 13 700 BP. The transfer-function reconstructs a less rapid cooling at the Allerød/Younger Dryas transition than other published records, possibly an artefact caused by the poor analogue situation during the earliest Younger Dryas, and an abrupt warming at the Younger Dryas/Holocene transition. During the Allerød, two centennial-scale 1.5-2.0 ° C coolings are apparent in the record. Although chronologically not well constrained, the first of these cold events may be synchronous with the beginning of the Gerzensee Oscillation. The second is inferred just before deposition of the Laachersee tephra at Lac Lautrey and is therefore coeval with the end of the Gerzensee Oscillation. In contrast to the Greenland oxygen isotope records, the Lac Lautrey palaeotemperature reconstruction lacks a clearly defined Greenland Interstadial (GI) event 1d and the decreasing ...